If you give a moose a muffin - Numeroff, Laura Joffe; Bond, Felicia ([New York] : HarperCollins, 1991)
Chaos can ensue if you give a moose a muffin and start him on a cycle of urgent requests.
Sequel to: If you give a mouse a cookie.
"Ages 3-7"--Jacket.
"A Laura Geringer book."
Keywords: Moose -- Fiction